2015
DOI: 10.1386/tmsd.14.3.241_1
|View full text |Cite
|
Sign up to set email alerts
|

Pluriactivity, the Dutch disease and sustainable agriculture in Algeria

Abstract: Agriculture and rurality have come under severe pressure in the last few decades. The loss of agricultural land and, hence, farming, through urban expansion has been pervasive. As a consequence, farmers tend to engage in pluriactivity to supplement their low farm income. This study explores the pervasiveness and underlying motivation behind pluriactivity by Algerian farmers. Algeria is a particularly interesting case where agriculture has been hit by severe and unique challenges. In particular, Algerian farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In doing these, many agricultural programs like the Agrarian Reform (1971), in the mid-1970s, the government adopted socialist policies. These include the destructive ''revolution agraire'' /''agricultural revolution'' that entailed the nationalization of private land and the grouping of peasants into ''domaines socialites''/''socialist syndicate'' without land title (Bouchakour & Bedrani, 2015).…”
Section: The Type Of Farms the Agrarian Revolution (Ra)mentioning
confidence: 99%
“…In doing these, many agricultural programs like the Agrarian Reform (1971), in the mid-1970s, the government adopted socialist policies. These include the destructive ''revolution agraire'' /''agricultural revolution'' that entailed the nationalization of private land and the grouping of peasants into ''domaines socialites''/''socialist syndicate'' without land title (Bouchakour & Bedrani, 2015).…”
Section: The Type Of Farms the Agrarian Revolution (Ra)mentioning
confidence: 99%
“…The survey showed that the majority of farmers combined agricultural and external activities and that between 64 per cent and 84 per cent of farmers with off‐farm jobs eventually left agriculture (Chaulet ). More recently, Bouchakour and Bedrani () pointed to the increasing pressure on Algerian farmers to leave their farms and take up lucrative employment or business in nonagricultural sectors.…”
Section: Off‐farm Work Across the Globementioning
confidence: 99%